2015
DOI: 10.3892/ijo.2015.3051
|View full text |Cite
|
Sign up to set email alerts
|

EBP1 protein modulates the expression of human MHC class II molecules in non-hematopoietic cancer cells

Abstract: Many solid tumours including melanoma, glioblastoma, and breast carcinomas express MHC class II molecules (MHC II). The surface expression of these molecules confers to non-hematopoietic tumour cells the role of non-professional antigen presenting cells and the ability to potentially stimulate tumour-specific CD4+ T cell response. We studied EBP1, an ErbB3 binding protein, and the effects of p48 and p42 isoforms on the MHC II expression in U87 glioblastoma, M14 melanoma and MCF7 mammary carcinoma cell lines. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…The biological effects of EBP1 vary depending on cell type and context, although the precise mechanisms for the differential roles and regulation of EBP1 in different tissues have not been defined (Miao et al 2015;Pisapia et al 2015;Hwang et al 2016). Previous study showed that Ebp1 is weakly expressed in mouse skeletal muscles, and its expression is higher in activated versus quiescent satellite cells (Squatrito et al 2004;Pallafacchina et al 2010;Figeac et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological effects of EBP1 vary depending on cell type and context, although the precise mechanisms for the differential roles and regulation of EBP1 in different tissues have not been defined (Miao et al 2015;Pisapia et al 2015;Hwang et al 2016). Previous study showed that Ebp1 is weakly expressed in mouse skeletal muscles, and its expression is higher in activated versus quiescent satellite cells (Squatrito et al 2004;Pallafacchina et al 2010;Figeac et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…EBP1 belongs to the PA2G4 family of transcription factors, which appears to fulfill multiple diverse biological functions (Pisapia et al . ; Hwang et al . ; Ko et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It binds to rRNAs and ribosomes (Squatrito et al, 2006) and also supports ribosome biogenesis by interacting with the Pol I transcription factor TIF-IA (Nguyen le et al, 2015;Nguyen et al, 2019) and possibly with nucleolar nucleophosmin (Okada et al, 2007). Fourth, HsEbp1 also stabilizes several mRNAs by binding their 39UTRs (Bose et al, 2006;Zhou et al, 2010;Pisapia et al, 2015).…”
mentioning
confidence: 99%
“…Western blot analysis confirms the specific enrichment of EBP1 by A-ROD (Figure 8D) while we could not recapitulate the specificity for HNRNPK although this has been reported to bind specifically to some long ncRNAs (Gumireddy et al, 2013; Huarte et al, 2010) (Figure 8D). The EBP1 isoform p48 has been reported to act as a context-dependent transcriptional activator (Pisapia et al, 2015), and is found to bind RNA in the nucleus (Conrad et al, 2016). To address whether EBP1 can bind to the DKK1 locus and to which extent this is dependent on A-ROD we did ChIP for EBP1 with or without depletion of A-ROD using siRNA (Figure 8E).…”
Section: Resultsmentioning
confidence: 99%